Female entrepreneurs : the secrets of their success - Smythe, John, 1951-; Saunders, Ruth (Marketing consultant) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The comparative numbers between male- and female-led start-ups is stark. Ninety-one percent of venture capital money continues to fund businesses founded solely by men, with only one percent of venture capital money invested in businesses founded solely by women. Being a woman entrepreneur is not the preserve of wonder woman. It's for every woman who wants to make it happen. Female Entrepreneurs: The Secrets of Their Success encourages every woman who has dreamt of being an entrepreneur but hasn't yet taken the leap to take the first steps towards realising her dreams - as well as every woman who has not yet thought about running her own business to consider it. Additionally, it encourages the Government and the corporate world to recognise and embrace the huge value that female entrepreneurs bring to our society and economy. John Smythe and Ruth Saunders reveal the secrets of the success of fifty-two female entrepreneurs. They outline wisdom and insights to inspire budding entrepreneurs to take the leap and offer practical advice on what to think about when setting your business up for success as well as when considering whether to scale. They also provide top tips on how to play to women's inherent strengths and avoid the weaknesses women face - as well as how to stay sane and enjoy the journey. This practical, unique guide provides the encouragement, support and motivation any aspiring female entrepreneur could need to make those first steps towards the realisation of their ambitions. John Smythe and Ruth Saunders are both entrepreneurs themselves and regularly advise start-ups on how to launch and scale up for growth"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Businesswomen -- Great Britain -- Case studies; Entrepreneurship -- Great Britain -- Case studies; Women-owned business enterprises -- Great Britain -- Case studies; Success in business -- Great Britain -- Case studies; BUSINESS & ECONOMICS / Entrepreneurship